A practical methodology of design of off-line reservoirs for reducing maximum water levels in urban channels (2020)
Flooding can often occur in many places due to the increasing trend of rainfall events (climate change), the urbanization process of a catchment area, or by an undersized urban channel. Reservoirs are used for limiting flooding since they can store an enough water volume. This research presents a practical procedure for sizing off-line reservoirs with an application in urban channels for places with space limitations. A complete formulation is presented, which can be easily used for designers and engineers for computing dimensions of off-line reservoirs. The formulation is applied to a case study located at the Cartagena de Indias, Colombia.